Influence of La3+ substitution on structure, morphology and magnetic properties of nanocrystalline Ni-Zn ferrite - Dasan, Y.K. (Public Library of Science, 2017)
Lanthanum substituted Ni-Zn ferrite nanoparticles (Ni0.5 Zn0.5 Lax Fe1-x O4 ; 0.00 ôxô 1.00) synthesized by sol-gel method were presented. X-ray diffraction patterns reveal the typical single phase spinel cubic ferrite structure, with the traces of secondary phase for lanthanum substituted nanocrystals. In addition, the structural analysis also demonstrates that the average crystallite size varied in the range of 21-25 nm. FTIR spectra present the two prominent absorption bands in the range of 400 to 600 cm-1 which are the fingerprint region of all ferrites. Surface morphology of both substituted and unsubstituted Ni-Zn ferrite nanoparticle samples was studied using FESEM technique and it indicates a significant increase in the size of spherical shaped particles with La3+ substitution. Magnetic properties of all samples were analyzed using vibrating sample magnetometer (VSM). The results revealed that saturation magnetization (Ms ) and coercivity (Hc ) of La3+ substituted samples has decreased as compared to the Ni-Zn ferrite samples. Hence, the observed results affirm that the lanthanum ion substitution has greatly influenced the structural, morphology and magnetic properties of Ni-Zn ferrite nanoparticles. © 2017 Dasan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.